Semantic deficits in amyotrophic lateral sclerosis. Issue 1 (March 2015) - Leslie, Felicity V. C.; Hsieh, Sharpley; Caga, Jashelle; Savage, Sharon A.; Mioshi, Eneida; Hornberger, Michael; Kiernan, Matthew C.; Hodges, John R.; Burrell, James R.
Abstract: Our objective was to investigate, and establish neuroanatomical correlates of, semantic deficits in amyotrophic lateral sclerosis (ALS) and amyotrophic lateral sclerosis-frontotemporal dementia (ALS-FTD), compared to semantic dementia (SD) and controls. Semantic deficits were evaluated using a naming and semantic knowledge composite score, comprising verbal and non-verbal neuropsychological measures of single-word processing (confrontational naming, comprehension, and semantic association) from the Sydney Language Battery (SYDBAT) and Addenbrooke's Cognitive Examination – Revised (ACE-R). Voxel based morphometry (VBM) analysis was conducted using the region of interest approach. In total, 84 participants were recruited from a multidisciplinary research clinic in Sydney. Participants included 17 patients with ALS, 19 with ALS-FTD, 22 with SD and 26 age- and education-matched healthy controls. Significant semantic deficits were observed in ALS and ALS-FTD compared to controls. The severity of semantic deficits varied across the clinical phenotypes: ALS patients were less impaired than ALS-FTD patients, who in turn were not as impaired as SD patients. Anterior temporal lobe atrophy significantly correlated with semantic deficits. In conclusion, semantic impairment is a feature of ALS and ALS-FTD, and reflects the severity of temporal lobe pathology.